EFFECT OF CONJOINT FAMILY THERAPY ON VALUE REORIENTATION AMONG YOUTHS FROM DYSFUNCTIONAL FAMILIES IN ABA METROPOLIS, ABIA STATE - AGHADINAZU, Rebecca E.; NWACHUKWU, Catherine I. (Journal of Professional Counselling, 2024)
The study examined the impact of conjoint family therapy on value reorientation among youths from dysfunctional families in Aba Metropolis, Abia State, Nigeria. A quasi-experimental research design was used in the study. Two (2) research questions and one corresponding hypothesis raised were tested at 0.05 level of significance. The study participants comprised of all families in the Aba metropolis with dysfunctional characteristics. The sample was 46 families with dysfunctional characteristics. The tool used to gather data was a researcher-developed instrument entitled “Value Reorientation and Family Dysfunctional Questionnaire (VRFDQ)”. The reliability coefficient, was 0.72. At the 0.05 level of significance, the obtained data were analyzed using Mean and Analysis of Covariance (ANCOVA) to test the hypotheses. Findings revealed that the mean responses of the families exposed to therapy and the control group differed significantly. Therefore, it was concluded that the conjoint family therapy approach is effective in combating dysfunctional characteristics among families and had an impact on how young people from such families reoriented their values. Thus, it was recommended among others that value re-orientation programmes, seminars, and workshops on healthy family living should be propagated by professional counsellors, churches, and NGOs to curb dysfunctionality among families.